2018
DOI: 10.1111/josh.12618
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Measuring Intentions to Use Best Practices: A Longitudinal Study Among Teachers Supporting Students With Autism

Abstract: The findings illustrate that the strength of intentions, which varies depending on the specific practice, can predict implementation. More generally, the studies demonstrate how measures of intention can aid efforts to identify implementation barriers. The approach taken can be applied to study implementation of any practices designed to improve student health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 20 publications
2
76
0
Order By: Relevance
“…It is not clear how EI clinicians working in a service system that is planning a wide-scale implementation will incorporate the program into their existing practice. Previous studies have found significant variation in educators' motivation to adopt new evidence-based practices within large-scale rollouts such as this one [18]. Associated barriers to implementing evidence-based practices are exacerbated in large under-resourced service settings, like the early intervention system in Philadelphia [29,30].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is not clear how EI clinicians working in a service system that is planning a wide-scale implementation will incorporate the program into their existing practice. Previous studies have found significant variation in educators' motivation to adopt new evidence-based practices within large-scale rollouts such as this one [18]. Associated barriers to implementing evidence-based practices are exacerbated in large under-resourced service settings, like the early intervention system in Philadelphia [29,30].…”
Section: Introductionmentioning
confidence: 92%
“…1) [15][16][17]. Previous work finds substantial variability in teachers' and clinicians' intentions to implement a new practice, and that intentions to implement a new practice are associated with its later implementation [16,18]. Understanding EI clinicians' intentions to implement parent coaching and whether these intentions are driven by attitudes, norms, and self-efficacy can lead to tailored implementation strategies that target specific mechanisms to increase use of parent coaching.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, school mental health services are frequently not based on evidence for effectiveness [32][33][34][35]. Recent evidence shows that school mental health professionals' intentions to use EBP are strongly associated with subsequent use [36] and that implementation may be driven as much or more by individual-level determinants (e.g., attitudes) than by organizational processes [11]. BASIS employs strategies targeting each TPB component: (1) Strategic education about EBP and intervention fidelity to improve attitudes toward EBP, (2) Social influence techniques to alter perceptions of subjective norms, and (3) Motivational Interviewing techniques to enhance perceived behavioral control.…”
Section: Beliefs and Attitudes For Successful Implementation In Schoomentioning
confidence: 99%
“…This model has been used to understand and predict many health-related behaviors [ 9 ], and interventions aimed at improvements in health-related intentions have been associated with behavior change [ 10 ]. However, the TPB has only recently been examined in relation to the implementation of EBPs for children with ASD in community settings [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fishman and colleagues demonstrated public school teachers who reported strong intentions to use visual schedules, an EBP for children with ASD, were significantly more likely to be observed using them with their students than teachers who reported weaker intentions, providing support for the role of intentions in predicting behavior [ 11 ]. Further, teachers reported significant variability in their intentions to use four different EBPs following training.…”
Section: Introductionmentioning
confidence: 99%